Cholesterol Granuloma of External Auditory Canal: A Case Report - Mokhtarinejad, Farhad; Majdinasab, Niloofar; Hosseini Vajari, Ali (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2020)
Background: Cholesterol granuloma is a histological term used for the description of a tissue response to the presence of an irritant foreign body, i.e. a cholesterol crystal. we report a cholesterol granuloma occupying the EAC of a17 year old teenage girl. Case Presentation: A 17 years old teenage girl presented with active otorrhea in the right ear. On physical examination the pink mass was visible in the right ear canal and the radiologist reported an expansile well-marginated lesion. Conclusions: A cholesterol granuloma presenting as a mass. A CT scan, the following conditions were considered, and do not routinely require surgery